2018
DOI: 10.3390/ma11101840
|View full text |Cite
|
Sign up to set email alerts
|

Effects of PEG1000 and Sol Concentration on the Structural and Optical Properties of Sol–Gel ZnO Porous Thin Films

Abstract: ZnO porous thin films were synthesized as antireflection coatings via a sol–gel dip-coating method with polyethylene glycol (PEG1000) utilized as a polymeric porogen on alumina transparent ceramics. The pore formation mechanism of the ZnO porous thin films was proposed through thermal and Fourier transformation infrared spectrometer (FTIR) analyses. The effect of sol concentrations on crystal structure, microstructure, and optical properties was also discussed. The experiment results indicated that all the ZnO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Chen et al 33 studied the synergistic effects of polyethylene glycol and organic montmorillonite (PEG/OMMT) on PLA films, and found that PEG/OMMT improved the elongation at break, mechanical strength, and thermal stability of the films. Xu et al 34 prepared zinc oxide porous films with dip‐coating method and studied the effect of PEG‐1000 on it. It was observed that PEG‐1000 acted as polymeric porogen and promoted the formation of uniform pores in the film.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al 33 studied the synergistic effects of polyethylene glycol and organic montmorillonite (PEG/OMMT) on PLA films, and found that PEG/OMMT improved the elongation at break, mechanical strength, and thermal stability of the films. Xu et al 34 prepared zinc oxide porous films with dip‐coating method and studied the effect of PEG‐1000 on it. It was observed that PEG‐1000 acted as polymeric porogen and promoted the formation of uniform pores in the film.…”
Section: Introductionmentioning
confidence: 99%
“…For the matrix refractive index n ~ 1.46 (in the case of SiO 2 ), the porosity of 0.45–0.50 ensures n ~ 1.23 of a single-layer anti-reflective coating [ 19 ]. For this purpose, various pore-generating agents, such as surfactants, are used [ 20 , 21 ]. Determining the optimum gel temperature and annealing time is one of the challenges in achieving antireflective parameters on silicate glass.…”
Section: Introductionmentioning
confidence: 99%